Combination of Chinese medicinal formulas and chemotherapy for triple-negative breast cancer strengthens body resistance to eliminate pathogenic factors. Issue 51 (23rd December 2022) - Zhang, Yiyi; Mo, Jing-Wen; Lu, Hai-Zhen; Han, Ling-Ling; Liu, Chengjiang; Zhou, Yi
Abstract : Background: To evaluate the efficacy and safety of strengthening the body's resistance to eliminate pathogenic factors in Chinese medicinal formulas combined with chemotherapy (hereafter referred to as combined therapy [CT]) in triple-negative breast cancer. Methods: By searching the 7 electronic databases, PubMed, EMBASE, Web of Science, Cochrane Library, Chinese Academic Journal, Wanfang Database, and Chinese Science and Technology Journal, from the beginning of the establishment to April 2022 to identify eligible randomized controlled trial studies. Results: The meta-analysis showed that compared with chemotherapy, CT can effectively improve the objective remission rate (risk ratio [RR]: 1.39; 95% confidence interval [CI]: 1.28, 1.52; P  < .00001, I 2  = 3%), reduce the recurrence rate (RR: 0.33; 95% CI: 0.14, 0.78; P  = .01, I 2  = 0%) metastasis rate (RR: 0.48; 95% CI: 0.31, 0.73; P  = .0006, I 2  = 0%) and the incidence of toxic and side reactions, lower tumor marker levels, regulated T lymphocyte subset changes, and increased average progression-free survival (standardized mean difference: 2.78; 95% CI: 1.41, 4.14; P  < .0001, I 2  = 97%), and improve the quality of life (RR: 1.55; 95% CI: 1.21, 1.99; P  = .0005, I 2  = 52%). Conclusion: This study suggests that CT appears to be an effective and safe treatment approach. Although this conclusion requires further confirmation owing to insufficient quality of the included trials.